Porous chitosan membranes with high porosity shaped by solvent evaporation technique in water as a solvent and acetone as a non-solvent - Silva, Angelo Oliveira (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.